Larval Crassostrea bivalve and Artemia brine shrimp bioassays to assess toxicity and micropredation by the heterotrophic dinoflagellates Cryptoperidiniopsis brodyi and Pfiesteria piscicida from Australian waters - Park, TG; Bolch, CJS; Hallegraeff, GM (Journal of Plankton Research, 2007)
The capability of the heterotrophic Australian marine dinoflagellates Cryptoperidiniopsis brodyi and Pfiesteria piscicida to impact on larval Pacific oyster (Crassostrea gigas) and brine shrimp (Artemia salina) nauplii was investigated. An attractant response of the heterotrophs toward actively swarming Artemia was not observed and no mortality occurred. In contrast, the dinoflagellates became active and exhibited attacking behavior toward planktonic oyster larvae (below 1 mm size) within a few seconds. The oyster larvae survived 2500 cells mL-1 for 2 days, but mortality increased to 82-88% by day 12. Aqueous dinoflagellate cell extracts collected from the bioassay that induced oyster kills were tested in a further larval bivalve bioassay but no mortality was observed. Oysters over 2 mm in size survived the physical attack by the heterotrophs and remained alive during the bioassay period. Changes in zoospore and cyst abundances in the presence of oyster larvae were also documented. More actively swarming zoospores and 2.5-fold higher cell numbers were produced in the presence of oysters compared to control cultures. These results indicate that mortalities of the planktonic larvae can be induced by micro-predatory feeding behavior of C. brodyi and P. piscicida. The Author 2007. Published by Oxford University Press. All rights reserved.